The Introduction of Plantations into East Sumatra and its Socio-economic Impacts, 1863-1929 - Pham Van Thuy (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The goal of this article is to examine the introduction of plantations into East Sumatra (Indonesia) in the late nineteenth and early twentieth century. Attention is given to the five most important plantation crops, namely tobacco, rubber, oil palm, tea, and fiber. The article analyzes the economic and social transformation of the region as a consequence of the rapid expansion of plantations. Within a short period of time, East Sumatra emerged to become one of the most dynamic economic regions of Southeast Asia. The development of the region and the needs of a source of protection for Dutch planters in face of fierce competition from other Western companies and local resistance encouraged the Dutch colonial government to establish effective authority in East Sumatra. Received 4th June 2020; Revised 15th September 2020; Accepted 26th September 2020